2020
DOI: 10.14744/tjtes.2020.25668
|View full text |Cite
|
Sign up to set email alerts
|

The effect of traffic accidents on pregnancy: is hospitalization necessary in every case?

Abstract: BACKGROUND: This study aimed to show whether it is necessary to hospitalize pregnant women who have been involved in traffic accidents. METHODS:Patients at a hospital in Istanbul, Turkey, who underwent traffic accidents between 2012 and 2018 were studied, and pregnant patients' files were evaluated. Demographic and obstetric features of patients, type of accident, type of trauma, Glasgow Coma Score, whether or not hospitalization were examined, the response of patients to hospitalization, and the obstetric and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…A possible explanation for this phenomenon might be that such women had no complications and they s assessed themselves that they did not need any extra treatment after the MVCs. 26 We found that pregnant women who visited the clinic but had no injury-related diagnosis after MVCs were also at increased risk of adverse pregnancy outcomes, including premature rupture of membranes, placental abruption, antepartum haemorrhage and caesarean delivery, compared with those who were not involved in MVCs. Our findings broadly support the work of a previous study, in which crashes resulting in no injury could increase the risk of adverse pregnancy outcomes.…”
Section: Original Researchmentioning
confidence: 81%
See 1 more Smart Citation
“…A possible explanation for this phenomenon might be that such women had no complications and they s assessed themselves that they did not need any extra treatment after the MVCs. 26 We found that pregnant women who visited the clinic but had no injury-related diagnosis after MVCs were also at increased risk of adverse pregnancy outcomes, including premature rupture of membranes, placental abruption, antepartum haemorrhage and caesarean delivery, compared with those who were not involved in MVCs. Our findings broadly support the work of a previous study, in which crashes resulting in no injury could increase the risk of adverse pregnancy outcomes.…”
Section: Original Researchmentioning
confidence: 81%
“…However, pregnant women who did not seek clinical treatment had no significant risk of adverse pregnancy outcomes. A possible explanation for this phenomenon might be that such women had no complications and they s assessed themselves that they did not need any extra treatment after the MVCs 26…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, few studies have addressed the characteristics of pregnant women involved in MVC in Asian countries. Even a study conducted in Turkey showed that 73% of patients were involved in car accidents (Soysal et al 2021 ). This can lead to misunderstandings regarding the appropriate target population, mainly because of notable differences in road conditions and the type of vehicle used between different countries.…”
Section: Introductionmentioning
confidence: 99%